Counter-flow microfluidic fuel cell with trapezoidal electrodes. (March 2023) - Li, Li; Ling, Lei; Xie, Yajun; Shan, Shuai; Bei, Shaoyi; Zheng, Keqing; Xu, Qiang
Abstract: Counter-flow microfluidic fuel cell suffers from severe non-uniform reaction rate distribution which leads to a poor contribution of the electrode outer part to the cell performance. In the present study, a novel trapezoidal electrode is designed for counter-flow microfluidic fuel cell to ameliorate its inferior performance. Superiority of the trapezoidal electrode over the conventional rectangular electrode is examined based on systematic numerical analyses and the results demonstrate that the cell with isosceles trapezoidal electrodes operated at 60 μ L m i n - 1 can even perform better than that with rectangular electrodes operated at a much higher flow rate (300 μ L m i n - 1 ). Mechanism behind the excellent performance of trapezoidal electrode is attributed to the synergistic effects of the enlarged active region, reduced ionic resistance and distinctive fluid distribution. Further optimization studies prove that isosceles trapezoidal design is preferred to the right-angled trapezoidal design owing to the more uniform fluid distribution and appropriate top length is suggested under the comprehensive consideration of electrode performance, fluid stability and operation feasibility. Conclusions indicate that the present trapezoidal electrode is more suitable for counter-flow microfluidic fuel cell and deserves further development.